Implementation of Agile Governance Principles Through the Village/Township Monograph Digitization Program in Bantaeng Regency - Shernylia Maladevi (Iapa Proceedings Conference, 2022)
The Government of Indonesia, through Bappenas, launched the Village/Township Monograph Digitization (DMD/K) program in 2020. This program is an effort to digitally document data in villages/twonship so that it can be processed and analyzed as a basis for planning and decision making. Bantaeng Regency was selected as one of the regions implementing this program. This study aims to determine the extent of the implementation of the principles of Agile Governance through the village/township monograph digitization program in Bantaeng Regency. Researchers use a qualitative approach with data collection techniques through observation, interviews and documentation. Data analysis is based on the agile governance theory proposed by Luna et al, (2015). The results of the study indicate that the implementation of agile governance is considered not optimal, there are five principles that have been effective. These principles include: good enough governance, business driven, human focused, systematic & adaptive approach and simple design & continuous refinement. While there is one other principle that is still not running optimally, namely the principle based on quick wins. This is because there is still a need for improvements to the Village/ township SEPAKAT application as the main supporter in this program, and local government commitment is needed in guarding this program by providing adequate data infrastructure facilities. It is hoped that the results of the analysis of the principles of agile governance can be an effort to further improve the quality of government services to the community, especially for the poor in Bantaeng Regency.